HOW BEHAVIORAL FACTORS INFLUENCE ESG DECISION-MAKING IN CORPORATE FINANCIAL STRATEGIES - ZAKHARKIN, Oleksiі; ZAKHARKINA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the behavioral dimension of ESG (Environmental, Social, and Governance) integration in corporate financial strategies, emphasizing the role of non-economic factors in decision-making processes. While most studies to date have focused on financial or regulatory incentives, this research shifts attention to behavioral determinants such as cognitive biases, leadership traits, organizational culture, and stakeholder pressure. These factors are positioned not as alternatives, but as critical complements to traditional economic drivers of ESG-oriented financial behavior. Through an interdisciplinary literature review and analytical generalization, the study identifies four key groups of behavioral factors that influence ESG decision-making: 1) cognitive biases (short-termism, risk aversion, herding behavior, confirmation bias), 2) leadership characteristics (ethical orientation, narcissistic traits, demographic diversity, leadership), 3) organizational norms and culture (value systems), and 4) stakeholder pressures interpreted through behavioral lenses. The interaction between these dimensions often explains variations in ESG commitment across firms facing similar external conditions. To systematize the findings, the authors propose an integrated matrix of behavioral determinants and managerial levers aimed at strengthening ESG alignment in financial strategies. This tool can assist corporate leaders in identifying internal barriers to sustainable finance and designing behavioral interventions such as incentive structures, leadership development, or cultural transformation to foster long-term ESG integration. The results of the study contribute to a deeper understanding of why ESG practices succeed or fail in the financial domain. They also provide practical recommendations for executives seeking to advance responsible finance through better alignment of internal decision-making with sustainability goals.
Keywords: ESG principles; behavioral finance; cognitive biases; financial strategy; corporate governance